Application of Critical Path Analysis in Forestry Projects - Suri, S. K. (Indian Forester, 1974)
In the recent past, management science has developed a new tool, known as critical path analysis, for the planning, scheduling and control of the complex projects. This technique is being gradually adopted by many organizations because of its simplicity, powerful logic and effective results. There is ample scope of adopting this technique in forestry projects. This paper describes, briefly, the technique and discusses the scope of its applicability in forestry projects.